Simulation of speed control brushless DC motor using gaussian fuzzy logic controller - Abd Karim, Nurliana (2014)
This paper presents a control scheme of a Fuzzy Logic for the brushless direct current (BLDC) motor drives. The BLDC motor has some advantages compare to others type of motors. However, the nonlinearity of this motor drive characteristics cause it is difficult to handle using conventional proportional-integral-differential (PID) controller. In order to overcome this main problem, Fuzzy Logic controller with a Gaussian membership function is developed. The mathematical model of BLDC motor is derived. The controller is designed to tracks variations of speed references and stabilizes the output speed during load variations. The effectiveness of the proposed method is verified by develop simulation model in Matlab Simulink software. The simulation results show that the proposed Fuzzy Logic controller (FLC) produce significant improvement control performance compare to the PID controller for both condition controlling speed reference variations and load disturbance variations.